Neck and shoulder pain among operation and maintenance workers of selected power supply enterprises - Zhang, Dan; Zhu, Baoyu; Li, Jiajie; Li, Hongyan; Gao, Yang; Liang, Zhanhui; Chen, Qingsong (Huan jing yu zhi ye yi xue = Journal of environmental & occupational medicine, 2023)
Background Power grid is a basic industry of national economy. The occupational health problems among operation and maintenance workers in this industry have become increasingly prominent in recent years, and they should receive enough attention. Objective To estimate the prevalence of work-related musculoskeletal disorders (WMSDs) of neck and shoulder among operation and maintenance workers of power supply enterprises, and analyze related influencing factors. Methods From March to June 2021, a total of 1433 operation and maintenance worker from 10 power supply enterprises in three provinces of North China were selected as research subjects using cluster sampling method. A revised Musculoskeletal Disorders Questionnaire was used to investigate the prevalence and ergonomic factors of neck and shoulder pain in the past year. χ2 test and logistic regression model were used to explore influencing factors of neck and shoulder pain among operation and maintenance workers. Results A total of 1343 valid questionnaires were recovered and the effective recovery rate was 93.72%. The neck pain prevalence was 66.0% (886 cases) and the shoulder pain prevalence was 54.1% (727 cases). The multiple logistic regression analysis results showed that often/very often long-time sitting (OR=1.864, 95%CI: 1.236-2.811; OR=1.659, 95%CI: 1.091-2.524), sometimes holding awkward postures (OR=1.695, 95%CI: 1.294-2.219; OR=1.596, 95%CI: 1.218-2.092), often/very often holding awkward postures (OR=2.416, 95%CI: 1.618-3.607; OR=2.058, 95%CI: 1.405-3.015), long-time slight neck tilting forward (OR=1.327, 95%CI: 1.023-1.722; OR=1.571, 95%CI: 1.221-2.022), long-time elbows bending (OR=1.327, 95%CI: 1.023-1.722; OR=1.506, 95%CI: 1.112-2.040) and department or team staff shortages (OR=1.578, 95%CI: 1.153-2.161; OR=1.831, 95%CI: 1.320-2.539) were associated with higher neck and shoulder pain prevalence rates. While exercise (OR=0.630, 95%CI: 0.492-0.809; OR=0.707, 95%CI: 0.557-0.899) was associated with lower neck and shoulder pain prevalence rates. Doing same work every day (OR=1.704, 95%CI: 1.305-2.225) was associated with a higher neck pain prevalence rate. Awkward postures with ineffectual force (OR=1.808, 95%CI: 1.226-2.665) and often keeping arms above shoulders (OR=1.424, 95%CI: 1.017-1.992) were associated with a higher shoulder pain prevalence rate. Conclusion The prevalence rates of neck and shoulder pian are high among operation and maintenance workers of power supply enterprises in selected three provinces of North China, and the main associated factors include individual factors, awkward work postures, and labor organization.